The World book encyclopedia. - World Book-Childcraft International (Chicago : World Book-Childcraft International, 1982)
An encyclopedia designed especially to meet the needs of elementary, junior high, and high school students.
Australasia suppl. (2 v.) and British Isles suppl. (2 v.) are each numbered as v. 23-24.
Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries